Solution‐Processable Perovskite Solar Cells toward Commercialization: Progress and Challenges - Wang, Peng; Wu, Yihui; Cai, Bing; Ma, Qingshan; Zheng, Xiaojia; Zhang, Wen‐Hua (Advanced functional materials, 2019)
In the last few years, organometal halide perovskites (OHPs) have emerged as a promising candidate for photovoltaic (PV) applications. A certified efficiency as high as 23.7% has been achieved, which is comparable with most of the well‐established PV technologies. Their good solubility due to the ionic nature enables versatile low‐temperature solution processes, including blade coating, slot‐die coating, etc., most of which are scalable and compatible with roll‐to‐roll large‐scale manufacturing processes. The low cost, high efficiency, and facile processable features make perovskite solar cells (PSCs) a very competitive PV technology. Despite the great progress, long‐term durability concerns, toxicity issues of both materials and manufacturing process, and lack of robust high‐throughput production technology for fabricating efficient large‐area modules are major obstacles toward commercialization. In this review, the recent progress of commercially available process of PSCs is surveyed, the underlying determinants for upscaling high‐quality PSCs from hydrodynamic characteristics and crystallization thermodynamic mechanism are identified, the influence of external stress factors on stability of PSCs and intrinsic instability mechanism in OHPs themselves is revealed, and the environmental impact and sustainable development of PSC technology are analyzed. Strategies and opportunities for large‐scale production of PSCs are suggested to promote the development of PSCs toward commercialization. Perovskite solar cells (PSCs) have emerged as a promising candidate for photovoltaic applications. This review summarizes the recent progress and discusses the obstacles for PSCs toward industrial production, including upscaling of high‐quality perovskites for efficient PSC modules, stability issue of PSCs, Pb substitution, and greener manufacturing process, which can promote the development of PSCs toward commercialization.